1992
DOI: 10.1021/bk-1992-0489.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Viscoelastic Properties of Cellulose Gels in Aqueous Alkali

Abstract: Detailed gelling conditions of cellulose-9 wt.% aqueous NaOH solution system were investigated by kinematic viscosity and light scattering methods. The system has two gelation temperatures in the room temperature region. The gel generated at a higher temperature region (HTG) is thermally irreversible, while the gel formed at a lower temperature shows thermal reversibility. Sol-gel transition cannot be explained in terms of liquid-liquid phase separation. The viscoelastic behavior accompanied with sol-gel trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, the larger (w + e 1 ) value corresponds to the larger degree of direct interaction and the value is lowest for aq HN0 3 . Keeping the above discussion in mind the result shown in Table II are summarized as follows: (1) The order of or is DMAc> DMSO»DMF>HN0 3 , hence the degree of the shielding effect from the interacted solvent (double bond part) is also in the above order, (2) the larger is the apparent 6 1 effect on CH carbon centered at mr triad sequence, unexpectedly the smaller is the w + e 1 effect, indicating the specific interaction between polymer and solvents, that is, this fact implies that -CN loses a nature of triple bond but does'nt make the n electron conjugate system, (3) the order of magnitude of b' is similar to band being HN0 3 »DMSO>DMF»DMAc, suggesting that the strength of interaction of solvent to -C = N is in the above order, (4) the order of magnitude of w + e', which is a measure for the degree of direct interaction to -CH proton in polymer, is DMAc>DMF» DMSO>HN0 3 , (5) 0' 2 -0' 1 evaluated by three methods is constant in most solvents (DMSO ( = 0.078 ppm)> DMF = DMAc ( = 0.073 ppm)» HN0 3 (0 ppm) (NaSCN (0.046---0.030 ppm) is positioned just between DMAc and HN0 3 )), (6) for all solvents 0' 2 -0' 1 =e holds (therefore, e=Oppm for HN0 3 ) when evaluated from the chemical shift difference between mmrr and rmrm peaks, and interestingly for organic solvents the evaluated 0' 2 -0' 1 (=e) values fall almost on 0.073-0.078, (7) some exceptions appear among the e values evaluated by four other methods depending on solvent nature (DMF, e ( = 0.097 ppm) evaluated from the chemical shift difference between mrrm and mrrr; DMSO, e ( = 0.058 ppm) evaluated from mmrm-mmrr); DMAc (0.024, 0.097 ppm) evaluated from mmrm-mmrr and mrrm-mrrr (or mrrr-rrrr), (8) Facts (5), (8), and (9) indicate that the interaction of HN0 3 with -C = N in mm and mr sequence of polymer is quite different from that for other organic solvents, which basically form n electron conjugate system with -C = N more or less, and might correspond to the facts reported by Yamazaki 16 (see, 4) and 5) in the present text). Facts (3) and ( 4) seem to correlate with so-called solvent power against highly isotactic PAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the larger (w + e 1 ) value corresponds to the larger degree of direct interaction and the value is lowest for aq HN0 3 . Keeping the above discussion in mind the result shown in Table II are summarized as follows: (1) The order of or is DMAc> DMSO»DMF>HN0 3 , hence the degree of the shielding effect from the interacted solvent (double bond part) is also in the above order, (2) the larger is the apparent 6 1 effect on CH carbon centered at mr triad sequence, unexpectedly the smaller is the w + e 1 effect, indicating the specific interaction between polymer and solvents, that is, this fact implies that -CN loses a nature of triple bond but does'nt make the n electron conjugate system, (3) the order of magnitude of b' is similar to band being HN0 3 »DMSO>DMF»DMAc, suggesting that the strength of interaction of solvent to -C = N is in the above order, (4) the order of magnitude of w + e', which is a measure for the degree of direct interaction to -CH proton in polymer, is DMAc>DMF» DMSO>HN0 3 , (5) 0' 2 -0' 1 evaluated by three methods is constant in most solvents (DMSO ( = 0.078 ppm)> DMF = DMAc ( = 0.073 ppm)» HN0 3 (0 ppm) (NaSCN (0.046---0.030 ppm) is positioned just between DMAc and HN0 3 )), (6) for all solvents 0' 2 -0' 1 =e holds (therefore, e=Oppm for HN0 3 ) when evaluated from the chemical shift difference between mmrr and rmrm peaks, and interestingly for organic solvents the evaluated 0' 2 -0' 1 (=e) values fall almost on 0.073-0.078, (7) some exceptions appear among the e values evaluated by four other methods depending on solvent nature (DMF, e ( = 0.097 ppm) evaluated from the chemical shift difference between mrrm and mrrr; DMSO, e ( = 0.058 ppm) evaluated from mmrm-mmrr); DMAc (0.024, 0.097 ppm) evaluated from mmrm-mmrr and mrrm-mrrr (or mrrr-rrrr), (8) Facts (5), (8), and (9) indicate that the interaction of HN0 3 with -C = N in mm and mr sequence of polymer is quite different from that for other organic solvents, which basically form n electron conjugate system with -C = N more or less, and might correspond to the facts reported by Yamazaki 16 (see, 4) and 5) in the present text). Facts (3) and ( 4) seem to correlate with so-called solvent power against highly isotactic PAN.…”
Section: Resultsmentioning
confidence: 99%
“…8 On the one hand, Kamide et a!. 9 reported that cellulose solutions obtained by dissolving cellulose with different crystal forms into a same solvent (9 wt% aq sodium hydroxide or cadoxen) exhibited quite different flow birefringence phenomena. Authors 10 also have pointed out that cellulose acetates dissolved in different polar solvents showed the specific solvation form depending on solvent employed.…”
mentioning
confidence: 99%